Gender and unpaid work: women's time and men's time - Perista, Heloísa (2002)
The purpose of this article is to make apparent the extent of unpaid work and to show how this is considered by men and women in Portugal. For this, the results of the 1999 Time Occupation Survey, carried out by the Instituto Nacional de Estatística (National Statistics Institute) are used.